Tingkat kemiskinan multidimensi rumah tangga buruh panen sawit rakyat di Kecamatan Air Rami, Kabupaten Mukomuko - Syifa Rohadatul Hasna; Nola Windirah; Agung Trisusilo; Gontom Citoro Kifli (University of Insan Cendekia Mandiri, 2025)
Poverty is not only seen from the inability in economic terms, but also the inability to fulfill education, health, and living standards. This study aims to determine the poverty status of households of smallholder oil palm harvest laborers in Air Rami Subdistrict, Mukomuko District, as well as the factors that influence multidimensional poverty. The research method used a quantitative approach with logistic regression analysis. The results showed that 30% of smallholder oil palm harvest laborer households were categorized as multidimensionally poor, with key indicators such as cooking fuel, years of schooling, and poor nutrition. Factors such as number of working days and health have a significant influence on multidimensional poverty, while variables such as land size, age, family dependents, alternative employment, and work experience are not significant. This study concludes that the multidimensional poverty of harvest labor households in Air Rami Sub-district is complex and multidimensional, not only related to income but also lack of access to basic needs.